New and little known species of the genus Orphnus MacLeay (Coleoptera: Scarabaeidae: Orphninae) from the East African Rift - Frolov, Andrey V. (Zootaxa, 2013)
The East African Rift, especially Eastern Arc Mountains, are renown for exceptionally high biodiversity and endemism (Olson & Dinerstein 1998, Burgess et al. 2007). About 20 species of the scarab beetle genus Orphnus MacLeay, 1819 (Coleoptera: Scarabaeidae: Orphninae) were described or recorded from this region (Paulian 1948, Petrovitz 1971) but many of them are still known only from the type series. Orphnus planicollis Petrovitz, 1971, was described from a single male specimen from “Nyassa-Land” with no additional data about this species published until now. Examination of the Orphninae material housed in European museums revealed additional specimens from southern Eastern Arc Mountains, Tanzania, which allowed us to clarify distribution of this rare species and study its sexual dimorphism and variability. In addition, two specimens of a new, putative sister species, O. demeyeri new species, were found in the material from Upemba National Park (south-eastern Democratic Republic of Congo).